Variation of axillary growth as respond of Morus spp. micropropagation using various concentration of Indonesian local solid substance - Yasinta Ratna Esti Wulandari; Laurensia Danis Anggradita (Society for Indonesian Biodiversity, 2020)
Abstract. Wulandari YRE, Anggradita LD. 2020. Variation of axillary growth as respond of Morus spp. micropropagation using various concentrations of Indonesian local solid substance. Biodiversitas 21: 80-85. The difficulties of growing Morus spp. makes it become one local plant that hard to cultivate conventionally even though it’s a beneficiary plant. Hence cultivation Morus spp. through tissue culture technique could help growing this plant. This research is aimed to design the optimal condition for micropropagation of local Morus spp. (Morus bombycis var. lembang, M. cathayana, M. multicaulis, and M. alba var. kanva-2) using agar-agar as Indonesian local solid substance. This solid substance is used as its cheap and easy to find compared to other solid substances. This research used MS medium supplemented with 0.1 ppm naphthalene acetic acid + 1.0 ppm benzyl aminopurine and various concentration of agar-agar (0.6%, 0.8%, 1.0%). Growth rate, axillary bud length and number, leaf number, callus formation and contamination were observed in this research. All those concentrations could be used for micropropagation of Morus spp. Agar concentrations of 0.8 and 1.0% showed better results than 0.6% because it showed the highest results.